Determination of Visfatin Level in Patients with Diabetes and Peripheral Neuropathy as Early Predicted Factor - Mohammed, Haneen A.; Ghudhaib, Kadhim K.; Mohsen, Firas Y. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
Peripheral neuropathy represents one of the common diabetic complications in patients with diabetes mellitus type 2 (DMT2). Peripheral neuropathy affects the feet, legs, hands, and arms. It was found that one-third to one-half of diabetics have peripheral neuropathy. The current study aimed to evaluate the level of visfatin in diabetic patient groups with or without peripheral neuropathy in comparison with healthy subjects to knowledge whether visfatin can be applied as a predictor factor for this type of disease complication. The study included 120 males and females ranging in age from 40 to 97 years old. (40 patients with type 2 diabetes, 40 patients with diabetic peripheral neuropathy, and 40 healthy people served as the control group.) All of the diabetes patients had a verified diagnosis (type 2). During the period from October 2021 to December 2021, the patients were assessed at the National Diabetes Center, Al-Mustansiriya University in Baghdad. Visfatin levels were tested using the ELISA technique, and HbA1c was assessed using Cobas C111. In patients, HbA1C levels are significantly higher (p≤0.05) than in controls. Males and females with DPN and DM have greater Visfatin mean values than the control group. Visfatin levels are strong indications for early diagnosis of diabetic neuropathy in both males and females, according to the current study.